How Enlightening and Reliable Are Cancer-Related Posts on Social Media Platforms? Opinions of a Sample of Nigerians - Nwafor, Jacob Njideka; Kanmodi, Kehinde Kazeem; Amoo, Babatunde Abiodun (Journal of Health and Allied Sciences NU, 2021)
Introduction On social media, several pieces of cancer-related information are being shared among people. This study aims to survey the Nigerian public, exploring their opinions on the influence (as per enlightenment) of cancer-related information on social media on them, and explore their opinions on the reliability of cancer-related posts they see on social media platforms.Methods This study was a descriptive cross-sectional online survey of 236 Nigerians, using an e-questionnaire. Collected data were analyzed using SPSS version 20 software (IBM Corp, New York, NY, United States).Results The majority (56.4%) of the respondents were females, 66.5% were within the age range of 20 to 29 years, and 92.4% had tertiary level of education. Virtually all (98.7%) of them had an Internet-enabled phone, and 99.6% were users of social media. The most used social media platform among them was WhatsApp while the most educative social media platform, according to them, was Facebook. Also, 96.6% (227/235) of those respondents who were social media users were of the opinion that social media is very useful for cancer education. However, only 68.5% (161/235) of them had learnt something new about cancer on social media platforms, of which 23.0% (37/161) rated the cancer information they have accessed on social media to be somewhat reliable.Conclusion Social media is highly influential in educating Nigerians on issues pertaining to cancer. However, not all cancer-related information posted on various social media platforms is reliable; hence, social media users should always take extra caution while consuming cancer-related posts on social media platforms.
Keywords: social media; cancer; education; information; reliability; Nigeria